Phylogeny of Yersinia pestis strains of the 4.ANT lineage from the Tuva mountains and adjacent plague foci - Elizaveta V. Stankovtseva; Eugeniy G. Oglodin; Dmitry B. Verzhutsky; Nadezhda S. Chervyakova; Ekaterina A. Naryshkina; Andrey V. Fedorov; Galina A. Eroshenko; Sergey V. Balakhonov; Vladimir V. Kutyrev (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
Introduction. The Tuva mountain plague focus (TMPF) in Russia has been continuously epizootically active since its discovery in 1964. The strains of Yersinia pestis isolated in this focus belong to the phylogenetic lineage 4.ANT of the antique biovar of the main subspecies. They are highly virulent and epidemically significant. The use of modern molecular genetic technologies will make it possible to determine the population structure of 4.ANT strains in the TMPF.